Evaluasi proksimat formula Makanan Pendamping ASI berbasis tepung hati ayam dan ikan teri untuk pencegahan stunting pada balita - Utami, Fista; Wahyuni, Endang Sri; Putri Sejati, Nawasari Indah; Ramadanti, Rivana Oktavia (Poltekkes Kemenkes Aceh, 2025)
Background: One approach to preventing stunting among toddlers is by providing complementary food (MP-ASI) made from nutrient-dense local ingredients, particulary those rich in animal-source protein. Chicken liver and anchovy power are high protein local food products that are relatively inexpensive and accessible, making them promising candidates for use as innovative ingredients or formulations in complementary feeding.Objectives: to evaluate the physical characteristic and proximate composition of a complementary food formula based on chicken liver and anchovy flour, and to assess its potential in fulfilling the nutritional needs of toddlers.Methods: An experimental design a Completely Randomized Design (CRD) with 3 replications. Proximate analysis was conducted at the Food Technology Laboratory of Politeknik Negeri Lampung, using standard methods from the Association of Official Analytical Chemists (AOAC) to determine moisture, ash, fat, protein, and carbohydrate contents of the MP-ASI formula.Results: The analysis revealed that the MP-ASI formula contained 8,26% moisture, 65,58 g/100 g protein, 12,,74 g/100 g fat, 8,26% ash, and 5,16 g/100 g carbohydrate. The nutritional composition of the formula meets the daily requirements for toddlers, providing more than 2-3 times the recommended protein intake and fulfilling 25,48% - 28,31% of the recommended fat intake. Although the carbohydrate content is less than 3%, the high ash content indicates a considerable amount of essential minerals, particularly iron and calcium.Conclusion: T Based on its nutritional composition, the formula demonstrates strong potential as a nutrient-dense MP-ASI ingredient for stunting prevention interventions. Future studies are recommended to analyze micronutrient content (iron, calcium, zinc, vitamin A, omega-3), as well as food cost and acceptability in toddlers.